Pemanfaatan Web Blog dan YouTube sebagai Media Pembelajaran Jarak Jauh Program Studi Desain Grafis - Muhammad Sholikhan; Eko Siswanto (STEKOM PRESS, 2020)
Learning media is a medium used in teaching and learning activities. As is known, the world is currently experiencing a Covid-19 pandemic so teaching and learning activities are carried out online. One of the media that can be used as distance learning is a web blog. Web blogs are chosen because they do not require a lot of money to create and can be combined with other media such as YouTube. This study aims to produce a web blog as a distance learning media for graphic design study programs. Because the lecture material uses more application practice, the web blog and YouTube media are very appropriate to use. This is in accordance with the results of the questionnaire distributed to graphic design students in semester 3 and 5 of STEKOM University regarding the use of a web blog. From 38 respondents and after being calculated based on existing references, the final score was 88.42% so that this web blog was in the